Effect of Cyclamen Perciscum extract on the inhibition of amoebic dysentery in mice: Experimental study - Samia Khalil Mahmood; Mohammad Mossa; Khalaf Y. Shamkhy; Falah Hanash Nahar; Rabab Qassim Saqir; Imad Ibrahim Ali Al-Sultan (Design for Scientific Renaissance, 2012)
Hot and cold alcoholic extract of Cyclamen Perciscum plant were used in concentrated extracts (150, 300 and 450 mg/kg body weight) in an experimental trial to look for its effectiveness and inhibitory action for Entamoeba histolytica .This protozoon parasite is the cause of Amoebic Dysentery in humans and animals. The disease is categorised by the International Health Organization as one of the most ten dangerous communicable diseases. Following the experimental infection with this parasite to a Swiss mice type (Balb C), the results have shown in general a significant effectiveness of hot alcoholic extract in comparison with the cold alcoholic extract of Cyclamen Perciscum . Slight differences among the extracts used to treat infected mice with Entamoeba histolytica or to inhabit parasitism with the control group is demonstrated in all aspects of investigation carried throughout this experimental study.